Postcolonial literature and the aesthetic of madness and violence : an analysis of nine african francophone and anglophone novels of post independance period - (:unkn) unknown (My University, 2013)
African literature of french and english expression appears today under deconstruction of european models. Originated from a context made of violence and real genocide of African cultures which has produced an identity chaos, this literature is marked nowadays by the motives of madness and violence. The nine novels on which this study is based correspond to this category ofafrican novel. It shows the various manifestations of madness and violence: segmented narrative structures, written language (French and English) damaged by African languages, themes sustainedby violence and madness. The authors of these texts have chosen to use characters that presentsymptoms of mental illness, extreme violence, genocides, civil wars, dictatorial regimes held by unconscious elites who exercise structural violence on people. Briefly, these texts bring us deeply in a real chaotic universe in their content as well as on their forms.This work demonstrates:- First, that violence in postcolonial era is provoqued on one band by the quest of power which always occurs by the elaboration of stereotypes through which an individual or a group is attributed negative qualities, and on the other band, by the resistance presented by the marginalized against allforms of domination.- Secondly, that chaotic situation undergone by Africans nowadays -behavioral crisis, identity crisis, depersonalization- is originated not only from its pass full of physical, moral and cultural violence, but also from the political elites who are still mentally colonized and imitate the attitudes of the colonizers. - Thirdly, that madness and violence which manifest themselves by a real aesthetic revolution and reorientation of literary discourse suits themselves in the logic of postcolonial method which instructs a form of subversion, and deconstruction of inherited models from normative European center. In one word, the aesthetic of madness and violence is concerned with the matter of claiming the diff
Keywords: African Research